2023
DOI: 10.1007/s11250-023-03478-7
|View full text |Cite
|
Sign up to set email alerts
|

The knowledge, attitudes, and practices of smallholder cattle farmers concerning the epidemiology of bovine fasciolosis in the North West Province, South Africa

Abstract: Bovine fasciolosis has negative impacts on cattle production worldwide, more so on the African continent and especially in smallholder farming areas with limited level of awareness. A cross-sectional questionnaire-based survey was conducted to investigate the knowledge, attitudes, and practices concerning bovine fasciolosis among smallholder cattle farmers in the North West Province of South Africa. A total of 153 farmers were interviewed from three villages of the Moretele Local Municipality in Bojanala Distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…In fact, the youth prefer jobs in big cities while the elderly attach their employment to rural settlements. 20 In our study, we found that the respondents from larger-scale farms had significantly higher knowledge scores, but practice scores were not significantly different. Normally, when the farmers invest more in their livestock production, they should have better understanding of farm management, biosecurity and disease preventive measures.…”
Section: Discussionmentioning
confidence: 44%
“…In fact, the youth prefer jobs in big cities while the elderly attach their employment to rural settlements. 20 In our study, we found that the respondents from larger-scale farms had significantly higher knowledge scores, but practice scores were not significantly different. Normally, when the farmers invest more in their livestock production, they should have better understanding of farm management, biosecurity and disease preventive measures.…”
Section: Discussionmentioning
confidence: 44%
“…Trematode prevalence has increased worldwide due to climatic variations (Suwannatrai et al, 2017), resistance to anthelmintics (Vineer et al, 2020), and current agricultural practices (Shrestha et al, 2020). Fascioliasis infection is chronic, generating losses in the animal industry due to reduced meat and milk production, bovine fertility (Jaja et al, 2017), and confiscation of livers (Arias-Pacheco et al, 2020), especially in animals raised in extensive systems (Olaogun et al, 2023).…”
Section: Introductionmentioning
confidence: 99%